"Creating a world for Spirit": affectual infrastructures and the production of a place for affect. (February 2019) - Pile, Steve; Bartolini, Nadia; MacKian, Sara
Highlights: Utilizes original fieldwork to provide a detailed account of the emergence of affect in a spiritual situation. Introduces the original concepts of affectual forms and affectual infrastructures to account for the emergence of affect. Which, together, provides a novel approach to the problem of spirit communication. Grounded in an understanding of unconscious communication derived from psychoanalysis.